Heritage as Civic Pedagogy: Affective Governance and Ritual Learning in Post-Socialist Hanoi - Tran, Quoc Viet; Nguyen, Thi Thanh Hoa; Bui, Van Tuan; Nguyen, Van Phuong; Dang, Thi Anh Tuyet (Journal of Education Culture and Society, 2026)
Aim. This article examines how heritage functions as a mode of civic learning in post-socialist Vietnam through an ethnographic study of the Temple of Literature in Hanoi. Rather than treating heritage as a passive site of remembrance, the study explores how ritual atmospheres, embodied conduct, and affective coordination quietly train people to sense what is appropriate, trustworthy, and morally shared within rapidly transforming urban life. Methods. The research draws on twelve months of ethnographic fieldwork conducted between 2023 and 2024, combining participant observation, affective fieldnotes, emotional diaries, on-site recordings, and thirty-five semi-structured interviews with students, teachers, pilgrims, guides, and heritage staff. Analysis focused on affective rhythms, embodied adjustments, and moments where emotion organized moral recognition before explicit interpretation emerged. Results. The findings identify three interrelated mechanisms of civic learning. First, visitors learn embodied discipline through silence, slowed movement, and self-regulated conduct. Second, collective attunement emerges through shared affective adjustments that align strangers without direct instruction. Third, ethical reflexivity develops as individuals continue to participate in ritual practices while remaining simultaneously aware, uncertain, and reflective about belief itself. Together, these processes enable heritage to operate as a moral infrastructure that stabilizes forms of civic coexistence under post-socialist conditions of social acceleration and uncertainty. Conclusions. The study argues that heritage functions not only as cultural memory but as an affective technology through which civic sensibilities are continuously recalibrated. This perspective repositions civic learning beyond institutional education and suggests that moral life may be sustained through shared atmospheres, ritual rhythms, and everyday practices of affective coordination.